Identification of key taste components in two aromatic rice varieties by widely targeted metabolomics in China. Issue 2 (3rd October 2022) - Zhao, Luyao; Duan, Xiaoliang; Hou, Can; Liu, Hongbin; Sun, Hui
Abstract: Background and Objectives: Due to the lack of comprehensive evaluation of all metabolites in rice, the metabolic reasons for taste differences are unclear. Here, two local varieties Wuyoudao 4 (WYD) (rich‐sweet flavor) and Nanjing 9108 (NJ) (delicate‐sweet flavor) were selected for ultra‐performance liquid chromatography‐tandem mass spectrometry based widely targeted metabolomic analysis. Findings: WYD and NJ were clearly separated by principal component analysis and hierarchical clustering analysis, and 231 metabolites were different between the cultivars, including 35 amino acids and derivatives, 14 saccharides and alcohols, and 12 organic acids. Among them, glucose, fructose, arabitol, and xylitol, contributed mainly to the rich‐sweet flavor of WYD rice. Leucine, phenylalanine, tryptophan, isocitric acid, and malic acid were the dominant compounds in NJ rice, and therefore, contributed primarily to the delicate‐sweet flavor. Conclusions: Vital compounds of rich‐sweet for WYD, and delicate‐sweet for NJ were clear. The differential metabolites were significantly enriched in the glucosinolate biosynthesis, valine, leucine and isoleucine degradation, and 2‐oxocarboxylic acid metabolism pathways. Significance and Novelty: This study would provide fundamental insights into the taste formation compounds and mechanism of aromatic rice.